Apocalyptic Paul: Cosmos and Anthropos in Romans 5–8. Edited by Beverly Roberts Gaventa - Byrne, Brendan (The journal of theological studies, 2014)
This collection had its origin in a conference on Romans 5–8 hosted by the editor, Beverly Gaventa, at Princeton Theological Seminary, Princeton, NJ, in May 2012. It consists of eight chapters derived from plenary papers read at the conference, with an Afterword from the late J. Louis Martyn. In a brief Preface (pp. vii–ix) Gaventa, noting a shift away from Romans 5–8 in recent scholarship, states that the contributions invite readers to consider the cosmological and anthropological implications of the gospel that feature particularly strongly in this section of the letter., Martinus C. de Boer (‘Paul's Mythologizing Program in Romans 5–8 [pp. 1–20]) argues that Paul's concern in Romans 5–8 is not what Bultmann called ‘demythologization’ but rather ‘mythologization’.